A series of fetal reductions and their outcomes at a tertiary care center in North Karnataka: Fetal reduction series: A boon? - Yalagachin, Neha G; VR, Rashmi; TH, Sunita (Indian Journal of Case Reports, 2024)
Fetal reduction is a novel method that aims to reduce a higher-order gestation to lower-order pregnancy to reduce both maternal and perinatal adverse outcomes. One of the methods of fetal reduction is by intracardiac injection of KCl under ultrasound guidance. Here, we present a case series of eight women who had undergone fetal reduction. All of them were trichorionic triamniotic triplets at the time of reduction. In seven women, the reduction was done to twin gestation, whereas one reduction was to singleton pregnancy. Out of eight cases, only one carried to full term and underwent vaginal delivery. One case was lost to follow-up and 2 women underwent expulsion. A total of nine live births were reported with 8 babies going to the neonatal intensive care unit for low birth weight and preterm care. Fetal reduction is an important method that needs to be widely practiced and reported to improve maternal and perinatal outcomes in multifetal gestation.